The Influence Of Servicescape And Service Quality On Customer Satisfaction And Repurchase Intention At One Eighty Café In Bandung - Armayoga Mukti Al-ghifari; Ira Fachira (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2021)
Servicescape and Service Quality play essential roles in the sustainability of the hospitality industry, particularly in Bandung restaurant business. One-Eighty Café is in the heart of Bandung Tourism Area, which has to deal with tight competition, leading to a focus on improving these factors. This study aims to help One Eighty café to overcome the problem and retain its customers by enhancing Servicescape and Service Quality, leading to Customer Satisfaction and Repurchase Intention. The preliminary data using observation and qualitative methods, followed by a quantitative approach by questionnaire, which is expected to be completed by at least 200 respondents. Quantitative data will be analyzed with SEM analysis. The findings of this study are expected to show the relationship between Servicescape (i.e., ambience and interior layout and design) and Service Quality (i.e., tangible, reliability, responsiveness, assurance, and empathy) influence on Customer Satisfaction and Repurchase Intentions in details. The recommendations of this study are expected to respond to the specific elements that management should focus on to save costs and maximize Customer Satisfaction to retain customers.